Pengaruh Discovery Learning Berbantuan Media Papan Pecahan terhadap Pemahaman Penjumlahan dan Pengurangan Pecahan Siswa SD - Khoirotul Ainiyah; Wahyu Maulida Lestari; Muhammad Assegaf Baalwi (Universitas Khairun, 2026)
This study was motivated by the large number of students who struggle to fully understand the concept of fractions, particularly when it comes to adding and subtracting fractions by finding a common denominator. This study aims to analyze the effect of applying the Discovery Learning model assisted by the Pancah media on the ability to understand the concept of fraction operations in fifth-grade students. This study it used a quantitative approach with an experimental research design employing a one-group pretest-posttest design. The population in this study consisted of 26 fifth-grade students; however, the sample comprised 24 students because two students had special needs, so the sampling technique used was purposive sampling. Data collection was conducted through tests, while data analysis utilized IBM SPSS Statistics 26 to perform validity tests, reliability tests, normality tests, and hypothesis testing (t-test). Based on the data analysis results, the Asymp. Sig. (2-tailed) value was 0.00 < 0.05, so H0 was rejected and Ha was accepted. These results indicate that the application of the Discovery Learning model assisted by the Pancah media has a significant effect on the fifth-grade students’ conceptual understanding of fraction operations at SDN Sidokare I Sidoarjo.